High-strength stainless steel and multi-step cutter prepared from high-strength stainless steel

By using multi-step tools prepared with high-strength stainless steel, efficient molding of multi-step holes is achieved, and problems of long processing time and difficult to ensure accuracy in the prior art are solved, and processing efficiency and product quality are improved.

CN119800227APending Publication Date: 2025-04-11CHANGZHOU RONGXIN COMPOSITE MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510089499.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing processing technology takes a long time and the machining accuracy is difficult to ensure when processing multi-stage step holes. Conventional tools need to be replaced frequently when processing step holes of different types and sizes, which increases time and cost.

Method used

A multi-step tool prepared with high-strength stainless steel, which can achieve step hole molding through one hole drilling machining, and ensure the high strength and machining accuracy of the tool by adjusting the design and material components of the tool.

Benefits of technology

It realizes efficient molding of multi-stage step holes, reduces processing time and cost, improves product quality stability and yield rate, and ensures high strength and simplicity of operation of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800227A_ABST
    Figure CN119800227A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of stainless steel cutters, in particular to high-strength stainless steel and a multi-step cutter prepared from the high-strength stainless steel. The high-strength stainless steel is prepared through raw material blending, and then the multi-step tool is obtained through machining of the high-strength stainless steel. The multi-step cutter can achieve one-time punching machining forming of multi-step holes, can obviously improve the machining precision of products and guarantee the quality stability of the products, has the advantages of being easy to operate, high in machining efficiency and low in production cost, meets the machining requirements of diversified product structures, and is extremely suitable for application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel cutters, in particular to high-strength stainless steel and a multi-step cutter made thereof. Background Art

[0002] In the mechanical processing industry, various hole parts are often encountered. When processing parts with multi-level stepped holes, due to the high requirements for the size and shape and position tolerances of the stepped holes, during the production and processing, the conventional processing technology is to first use a drill or milling cutter to open a bottom hole, and then change the drill or milling cutter to open a countersink. This processing method takes a long time, and the coaxiality of the processed bottom hole and countersink must be guaranteed by the precision of the processing equipment.

[0003] Therefore, in view of such situations, the inventors have designed and prepared a multi-step tool, which can realize step hole forming through a single punching machine processing. And if you want to process step holes of different types and sizes, you only need to make corresponding tools according to the different types and sizes of step holes, which can greatly save time and cost. In order to ensure the processing accuracy of the multi-step tool, it is also necessary to ensure the strength of the multi-step tool to avoid interference with the workpiece.

[0004] In summary, in view of the existing processing methods, it is very necessary to design and invent a multi-step tool made of high-strength stainless steel with a simple structure and easy operation. Summary of the invention

[0005] The object of the present invention is to provide a high-strength stainless steel and a multi-step tool prepared therefrom to solve the problems raised in the prior art.

[0006] To achieve the above object, the first aspect of the present invention provides the following technical solutions: A high-strength stainless steel comprises the following components: by mass percentage, C≤0.05%, Cr 12-15%, Mn0.5-1.5%, Si 0.3-0.6%, P≤0.02%, S≤0.02%, Mo 0.5-1%, Ni 8-12%, Nb 0.05-0.15%, Re0.05-0.2%, reinforced composite material 2-6%, and the rest is Fe and unavoidable impurities, and the impurities are ≤0.03%; wherein Re includes but is not limited to a combination of one or more of La, Ce and Y.

[0007] Furthermore, the reinforced composite material is obtained by mixing the Fe / Ti / graphene composite material and the reinforced nanoparticles in a mass ratio of 4:(0.5-2).

[0008] Furthermore, the preparation method of the Fe / Ti / graphene composite material is as follows: (1) dispersing graphene in an ethanol solution to prepare a 1-5wt% graphene solution; (2) adding Fe powder, Ti powder and stearic acid to the graphene solution under nitrogen protection, ball milling for 1-3 days with a ball-to-material ratio of 40:1, and then drying the mixed solution to obtain a mixed powder; (3) adding the mixed powder into a columnar graphite mold, evacuating the mold, and hot pressing and sintering at 400-450°C and 120MPa for 1-5h to obtain a Fe / Ti / graphene composite material.

[0009] Furthermore, the mass ratio of the graphene, Fe powder and Ti powder is (0.02-0.04):1:1.

[0010] Furthermore, the amount of stearic acid added is 0.5-1% of the total mass of the material to be ground; it mainly plays a wetting role, making the grinding process more sufficient and uniform.

[0011] Furthermore, the reinforcing nanoparticles include but are not limited to any one of SiC, TiB2 and TiC.

[0012] Although a high content of C element can improve the strength of stainless steel, it will also combine with Cr to form carbide precipitation during the heat treatment process, which will significantly reduce the corrosion resistance of stainless steel; P element has a certain effect on enhancing the strength of stainless steel, but it will more often cause segregation of stainless steel, increasing its brittleness. If its content is too high, the prepared tool is very likely to crack; an appropriate amount of S element can improve the cutting and processing properties of stainless steel, but it will more often cause serious segregation of stainless steel; and S element can be used together with Mn, Mn and S will combine to form MnS, which can eliminate the segregation effect brought by S and has a certain effect on the strength of stainless steel, but if the MnS content is too high (i.e., S is excessive), the cutting performance of stainless steel will increase, affecting the relevant properties of the prepared tool, so the present invention strictly controls the C, P, and S elements in stainless steel; Cr and Ni are important elements in stainless steel. Cr can give stainless steel excellent corrosion resistance, and at the same time can also increase the hardenability of stainless steel and enhance its comprehensive strength after subsequent heat treatment. It has a great influence on the performance of stainless steel, but the Cr content also needs to be controlled. If its content is too high, σ phase will precipitate in the stainless steel, causing the toughness of the stainless steel to drop sharply; Ni element can change the crystal structure of stainless steel and form austenite crystal structure in stainless steel. It is an important factor affecting the strength and other properties of stainless steel, but too high Ni content will reduce the Ms point temperature in stainless steel, which will lead to an increase in the residual austenite content in the stainless steel and reduce the strength of the stainless steel. Therefore, the dosage of the two elements is comprehensively considered in the present invention, and the controlled dosage range is 12~15% for Cr and 8~12% for Ni respectively; Si element can be dissolved in ferrite and austenite to improve the hardness and strength of stainless steel. In order to ensure that the processability of stainless steel is not affected, its dosage should be controlled in the range of 0.3~0.6%; Mo element can cooperate with Cr element to enhance the hardenability and corrosion resistance of stainless steel. By adding a small amount of Mo, the strength of stainless steel can be significantly improved. Its dosage range should be controlled in 0.5~1%. As an important reinforcing component in the present invention, Nb element can combine with C element to form stable NbC, which ensures the grain refinement in the stainless steel structure and has a significant effect on the strength of stainless steel. At the same time, it can also reduce Cr 23 The formation of C6 plays a certain role in ensuring the corrosion resistance of stainless steel, and its dosage is controlled at 0.05~0.15%; At the same time, the present invention further adds a reinforced composite material, which is obtained by mixing a Fe / Ti / graphene composite material and reinforced nanoparticles; the Fe / Ti / graphene composite material improves the dispersion uniformity of graphene in the metal melt (graphene can improve the corrosion resistance of stainless steel on the one hand, and can enhance the lubrication and wear resistance of stainless steel on the other hand, which not only enhances the durability of the prepared tool, but also improves the surface quality of the product obtained by subsequent tool processing), and introduces the Ti element at the same time, the Fe / Ti / graphene composite material can cooperate with the Nb element, both of which can stabilize carbides with the C element performance, promote grain refinement, make the internal organization of stainless steel more compact, and play a role in enhancing the strength of stainless steel, but the amount of both graphene and Ti should not be too much; the reinforced nanoparticles act in the stainless steel organization, affecting the crystal structure, such as generating a cellular structure with a high dislocation density, which can significantly and effectively enhance the strength and other properties of stainless steel, but the amount should not be too much, otherwise a large number of long cracks will appear; therefore, the amount of the reinforced composite material is controlled in the range of 2-6% in the present invention; Re rare earth metal elements mainly play the role of purification and impurity removal in stainless steel. At the same time, they form stable compounds with ferrite to comprehensively enhance and improve the corrosion resistance and strength of stainless steel. The dosage is controlled at 0.05~0.2%.

[0013] Furthermore, the preparation method of the high-strength stainless steel is as follows: (1) weighing the required components of the high-strength stainless steel raw materials according to mass percentage; (2) adding each raw material component into a vacuum induction furnace, preheating at 15-20 kW for 5-10 minutes, then heating at 80-100 kW until the alloy material components are completely melted, and maintaining the molten state for 10-30 minutes, and finally refining at 20-35 kW for 30-60 minutes to obtain a mixed metal liquid; (3) the mixed metal liquid is cast and electroslag remelted to obtain a cast billet; (4) the cast billet is subjected to uniform heat treatment and solid solution treatment to obtain high-strength stainless steel.

[0014] Furthermore, the soaking treatment is as follows: heating the ingot to 1150-1280°C and keeping the temperature for 2-6 hours, then taking the ingot out of the furnace and air cooling it.

[0015] Furthermore, the solution treatment is as follows: heating the ingot after the soaking treatment to 1050-1100° C. and keeping the temperature for 5-15 minutes, then taking it out of the furnace and cooling it with water.

[0016] A second aspect of the present invention provides a multi-step tool made of the high-strength stainless steel.

[0017] Furthermore, the preparation method of the multi-step tool is: cutting and shaping, grinding and polishing, and nitriding high-strength stainless steel in sequence to obtain the multi-step tool.

[0018] Furthermore, the nitriding treatment is performed using plasma nitriding technology, and its parameters are set as follows: the working gas is ammonia, the working temperature is 450-550° C., the working pressure is 200-300 Pa, and the nitriding treatment is performed for 4-8 hours.

[0019] Nitriding the already formed multi-step tool can make the tool surface obtain a higher hardness, wear resistance, and corrosion resistance surface layer (Ti, Cr and other elements on the tool surface and N elements form extremely stable nitrides with super high hardness and strength), while its interior can still maintain its original toughness. The excellent performance of the surface layer improves the turning ability of the tool, enabling it to better process products with stable quality; generally, as the hardness of the metal increases, its brittleness will also increase, and the toughness of the tool after nitriding can well maintain its impact load resistance during the turning process, greatly avoiding its collapse during the turning process, and further ensuring the strength performance of the multi-step tool.

[0020] Furthermore, the multi-step tool includes three parts: a shank, a blade and a guide column; the shank is a cylindrical rod structure, the blade is a multi-step columnar structure, and the guide column is a cylindrical rod structure; step holes can be processed by the action of the blade.

[0021] Furthermore, in the embodiment of the present invention, the length of the hilt is 70 mm and the diameter is 30 mm.

[0022] Furthermore, in an embodiment of the present invention, the blade is specifically a two-step columnar structure, including a first blade section and a second blade section; wherein the length of the first blade section is greater than the length of the second blade section.

[0023] Furthermore, in the embodiment of the present invention, the length of the first blade section is 30 mm, and the diameter is 29 mm; the length of the second blade section is 15 mm, and the diameter is 46 mm.

[0024] Furthermore, in the embodiment of the present invention, the guide pillar has a length of 50 mm and a diameter of 17 mm.

[0025] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares high-strength stainless steel by blending raw material components and enhancing the composite material, and then processes and prepares a multi-step tool; the multi-step tool has a higher hardness and can be processed to obtain a product with better surface quality; 2. The multi-step tool prepared by the present invention can process multi-step holes at one time through one clamping, which reduces the number of tool changes and tool adjustments, simplifies the processing procedures, and greatly reduces the processing time; and through one-time processing and forming, not only the coaxiality of each hole segment in the multi-step hole is improved, but also the processing accuracy of the product can be improved, so that the quality stability of the product is good, the yield rate of the product is greatly improved, and the production cost of the enterprise is reduced; 3. The multi-step tool prepared by the present invention has the advantages of simple operation, convenient use, high processing efficiency and low production cost, which greatly meets the processing needs of diversified product structures and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of the structure of a multi-step tool prepared by the present invention; Figure 2 A physical picture of a multi-step tool prepared according to the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively: C, Cr, Mn, Si, P, S, Mo, Ni, Nb, Re, Fe, Y, SiC with an average particle size of 70 nm and a purity of Ti of ≥99% were purchased from Shanghai Xianxin New Materials Technology Co., Ltd.; Graphene purity ≥96%, single layer, thickness: 2~10nm, particle size: 1~50nm, purchased from Jining Lit Nanotechnology Co., Ltd.; Stearic acid, purity ≥98%, was purchased from Wuhan Jingbiao Technology Co., Ltd.

[0029] Example 1: A high-strength stainless steel: S1: Preparation of Fe / Ti / graphene composite material: (1) Disperse 0.3 parts of graphene in ethanol solution to prepare a 3 wt% graphene solution; (2) Under nitrogen protection, add 10 parts of Fe powder, 10 parts of Ti powder and 0.16 parts of stearic acid to the graphene solution, ball mill for 2 days, wherein the ball-to-material ratio is 40:1, and then dry the mixed solution to obtain a mixed powder; (3) Add the mixed powder into a columnar graphite mold, evacuate, and hot press sinter at 420°C and 120 MPa for 3 hours to obtain a Fe / Ti / graphene composite material; S2: preparing a reinforced composite material: mixing the Fe / Ti / graphene composite material and SiC in a mass ratio of 4:1 to obtain a reinforced composite material; S3: (1) Weigh the required components of high-strength stainless steel raw materials according to mass percentage; (2) Add each raw material component to a vacuum induction furnace, preheat it at 18 kW for 10 minutes, then heat it at 90 kW until the alloy material components are completely melted, and keep the molten state for 20 minutes, and finally refine it at 30 kW for 45 minutes to obtain a mixed metal liquid; (3) The mixed metal liquid is cast and electroslag remelted to obtain a cast billet; (4) Heat the cast billet to 1200℃ and keep it for 5 hours, then take it out of the furnace and cool it in air to complete the heat treatment, then heat it to 1080℃ and keep it for 10 minutes, then take it out of the furnace and cool it in water to complete the solid solution treatment to obtain high-strength stainless steel.

[0030] Example 2: A high-strength stainless steel and a multi-step tool made thereof: S1: Preparation of Fe / Ti / graphene composite material: (1) Disperse 0.2 parts of graphene in ethanol solution to prepare 2 wt% graphene solution; (2) Under nitrogen protection, add 10 parts of Fe powder, 10 parts of Ti powder and 0.16 parts of stearic acid to the graphene solution, ball mill for 1 day, wherein the ball-to-material ratio is 40:1, and then dry the mixed solution to obtain a mixed powder; (3) Add the mixed powder into a columnar graphite mold, evacuate, and hot press sinter at 400°C and 120 MPa for 1 hour to obtain a Fe / Ti / graphene composite material; S2: preparing a reinforced composite material: mixing the Fe / Ti / graphene composite material and SiC in a mass ratio of 4:0.5 to obtain a reinforced composite material; S3: (1) Weigh the required components of high-strength stainless steel raw materials according to mass percentage; (2) Add each raw material component to a vacuum induction furnace, preheat it at 18 kW for 10 minutes, then heat it at 90 kW until the alloy material components are completely melted, and keep the molten state for 20 minutes, and finally refine it at 30 kW for 45 minutes to obtain a mixed metal liquid; (3) The mixed metal liquid is cast and electroslag remelted to obtain a cast billet; (4) Heat the cast billet to 1200℃ and keep it for 5 hours, then take it out of the furnace and cool it in air to complete the heat treatment, then heat it to 1080℃ and keep it for 10 minutes, then take it out of the furnace and cool it in water to complete the solid solution treatment to obtain high-strength stainless steel.

[0031] Example 3: A high-strength stainless steel and a multi-step tool made thereof: S1: Preparation of Fe / Ti / graphene composite material: (1) Disperse 0.4 parts of graphene in ethanol solution to prepare a 4 wt% graphene solution; (2) Under nitrogen protection, add 10 parts of Fe powder, 10 parts of Ti powder and 0.16 parts of stearic acid to the graphene solution, ball mill for 3 days, wherein the ball-to-material ratio is 40:1, and then dry the mixed solution to obtain a mixed powder; (3) Add the mixed powder into a columnar graphite mold, evacuate, and hot press sinter at 450°C and 120 MPa for 5 hours to obtain a Fe / Ti / graphene composite material; S2: preparing a reinforced composite material: mixing the Fe / Ti / graphene composite material and SiC in a mass ratio of 4:2 to obtain a reinforced composite material; S3: (1) Weigh the required components of high-strength stainless steel raw materials according to mass percentage; (2) Add each raw material component to a vacuum induction furnace, preheat it at 18 kW for 10 minutes, then heat it at 90 kW until the alloy material components are completely melted, and keep the molten state for 20 minutes, and finally refine it at 30 kW for 45 minutes to obtain a mixed metal liquid; (3) The mixed metal liquid is cast and electroslag remelted to obtain a cast billet; (4) Heat the cast billet to 1200℃ and keep it for 5 hours, then take it out of the furnace and cool it in air to complete the heat treatment, then heat it to 1080℃ and keep it for 10 minutes, then take it out of the furnace and cool it in water to complete the solid solution treatment to obtain high-strength stainless steel.

[0032] Based on Example 1, Examples 4 to 5 and Comparative Examples 1 to 4 are provided as follows: Examples 4-5: Examples 4-5 are based on Example 1, and the following adjustments are made: the amounts of Nb and the reinforced composite material, as shown in Table 1 below; Comparative Example 1: Comparative Example 1 was adjusted based on Example 1 except that Nb was not added and the others remained unchanged; Comparative Example 2: Comparative Example 2 is adjusted based on Example 1: no reinforcing composite material is added, and the rest remains unchanged; Comparative Example 3: Comparative Example 3 is adjusted based on Example 1: Fe / Ti / graphene composite material is not added to the reinforced composite material, and other conditions remain unchanged; Comparative Example 4: Comparative Example 4 is adjusted based on Example 1: SiC is not added to the reinforced composite material, and the rest remains unchanged.

[0033] The component dosages of the high-strength stainless steel prepared in Examples 1 to 5 and Comparative Examples 1 to 4 are shown in Table 1:

[0034] Performance Test 1: The mechanical properties of the high-strength stainless steel prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested. The specific test results are shown in Table 2 below:

[0035] Result analysis: From the data in Table 2 above, it can be seen that the present invention prepares high-strength stainless steel (Example 1) with better hardness and strength by blending important raw material components (Nb, reinforced composite materials (including SiC, Fe / Ti / graphene composite materials)). Compared with the comparative examples, especially comparative examples 1 and 2, the high-strength stainless steel obtained in Example 1 has obvious improvements in tensile strength and hardness.

[0036] Based on the above test results of high-strength stainless steel, the high-strength stainless steel prepared in Example 1 was processed into a multi-step tool: (1) High-strength stainless steel is cut, formed, polished, and nitrided in sequence to obtain a multi-step tool; wherein the nitriding treatment is carried out using plasma nitriding technology, and its parameters are set as follows: the working gas is ammonia, the working temperature is 500°C, the working pressure is 250Pa, and the nitriding treatment is 6h; the handle length of the multi-step tool is 70mm and the diameter is 30mm; the blade: the length of the first blade section is 30mm and the diameter is 29mm, the length of the second blade section is 15mm and the diameter is 46mm; the length of the guide column is 50mm and the diameter is 17mm; (2) Since nitriding treatment is another technical point of the present invention, a multi-step tool is processed. The multi-step tool has a shank length of 70 mm and a diameter of 30 mm; a blade: the length of the first blade section is 30 mm and the diameter is 29 mm, and the length of the second blade section is 15 mm and the diameter is 46 mm; the guide column has a length of 50 mm and a diameter of 17 mm, and is not nitrided.

[0037] Performance Test 2: The multi-step tool prepared above was used for multi-step hole punching machining, and the accuracy was compared with that of the multi-step holes obtained by conventional machining process, as follows: (1) The surface luminosity test was carried out using a NEVIEW7300 scanning white light interferometer, and its size was used to characterize the accuracy of the multi-step hole. The smaller the surface luminosity, the smaller the surface roughness, and thus the higher the accuracy of the multi-step hole.

[0038] The specific results are shown in Table 3 below:

[0039] Result analysis: From the results in Table 3, it can be seen that the multi-step holes machined by the multi-step tool punching machine prepared by the present invention have better surface quality, which further shows that the multi-step tool prepared by the present invention has significantly superior practicality, greatly meets the processing needs of diversified product structures, and is suitable for promotion and application.

[0040] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-strength stainless steel, characterized in that: The high-strength stainless steel comprises the following components: by mass percentage, C≤0.05%, Cr 12~15%, Mn 0.5~1.5%, Si 0.3~0.6%, P≤0.02%, S≤0.02%, Mo 0.5~1%, Ni8~12%, Nb 0.05~0.15%, Re 0.05~0.2%, reinforced composite material 2~6%, and the rest is Fe and unavoidable impurities, and the impurities are ≤0.03%; Wherein, Re includes a combination of one or more of La, Ce and Y; the reinforced composite material is obtained by mixing the Fe / Ti / graphene composite material and the reinforced nanoparticles in a mass ratio of 4:(0.5~2).

2. The high-strength stainless steel according to claim 1, characterized in that: The preparation method of the Fe / Ti / graphene composite material is as follows: (1) dispersing graphene in an ethanol solution to prepare a 1-5wt% graphene solution; (2) adding Fe powder, Ti powder and stearic acid to the graphene solution under nitrogen protection, ball milling for 1-3 days with a ball-to-material ratio of 40:1, and then drying the mixed solution to obtain a mixed powder; (3) adding the mixed powder into a columnar graphite mold, evacuating the mold, and hot pressing and sintering at 400-450°C and 120MPa for 1-5h to obtain a Fe / Ti / graphene composite material.

3. The high-strength stainless steel according to claim 2, characterized in that: The mass ratio of the graphene, Fe powder and Ti powder is (0.02-0.04):1:1; the amount of stearic acid added is 0.5-1% of the total mass of the material to be ground.

4. The high-strength stainless steel according to claim 1, characterized in that: The reinforcing nanoparticles include any one of SiC, TiB2 and TiC.

5. The high-strength stainless steel according to claim 1, characterized in that: The preparation method of the high-strength stainless steel comprises the following steps: (1) weighing the required components of the high-strength stainless steel raw materials according to the mass percentage; (2) adding each raw material component into a vacuum induction furnace, preheating at 15-20 kW for 5-10 minutes, then heating at 80-100 kW until the alloy material components are completely melted, and maintaining the molten state for 10-30 minutes, and finally refining at 20-35 kW for 30-60 minutes to obtain a mixed metal liquid; (3) casting and electroslag remelting the mixed metal liquid to obtain a cast billet; (4) subjecting the cast billet to a uniform heat treatment and a solid solution treatment to obtain the high-strength stainless steel.

6. The high-strength stainless steel according to claim 5, characterized in that: The soaking treatment is as follows: heating the ingot to 1150-1280°C and keeping it for 2-6 hours, then cooling it in air; the solution treatment is as follows: heating the soaking treated ingot to 1050-1100°C and keeping it for 5-15 minutes, then cooling it in water.

7. A multi-step tool made of the high-strength stainless steel according to any one of claims 1 to 6, characterized in that: The preparation method of the multi-step tool is: cutting and shaping, grinding and polishing, and nitriding high-strength stainless steel in sequence to obtain the multi-step tool.

8. The multi-step tool made of high-strength stainless steel according to claim 7, characterized in that: The multi-step tool comprises a tool handle, a blade and a guide column; the tool handle is a cylindrical rod structure, the blade is a multi-step columnar structure, and the guide column is a cylindrical rod structure.

9. The multi-step tool made of high-strength stainless steel according to claim 8, characterized in that: The length of the handle is 70mm and the diameter is 30mm; the blade is specifically a two-step columnar structure, including a first blade section and a second blade section, wherein the length of the first blade section is greater than the length of the second blade section, specifically: the length of the first blade section is 30mm and the diameter is 29mm; the length of the second blade section is 15mm and the diameter is 46mm; the length of the guide column is 50mm and the diameter is 17mm.

10. The multi-step tool made of high-strength stainless steel according to claim 7, characterized in that: The nitriding treatment is carried out by plasma nitriding technology, and its parameters are set as follows: the working gas is ammonia, the working temperature is 450-550° C., the working pressure is 200-300 Pa, and the nitriding treatment is 4-8 hours.